Mídias Sociais, Adolescentes e Cidadania: Espaços de Representações e de Educação para a Mídia - Gomes, Joyce Galdino [UNESP] (2014)
This research, registered in Formative Processes and Practices in Education line, had the general objective of identifying and analyzing the social representation of adolescent students enrolled at Tannel Abbud, a Public High School located in the municipality of Presidente Prudente (SP), about the role of media, specially of a specific social media in particular, Facebook, in the construction of their concept of citzenship. In order to achieve this goal, the following specific objectives were set: identifying the frequency and nature of use of social media by adolescents in their daily lives; identifying the frequency and nature of use of social medias in the classrooms by the surveyed adolescents; identifying and analyzing the representations of adolescents on social medias, specifically Facebook, and identifying and analyzing the representations of adolescents on the concept of citzenship. The investigation took a qualitative approach with a descriptive-explanatory design and it will take the character of a stocktaking study, known as Survey. Data analysis was performed on the content analysis, aiming to contribute to the understanding of this recent phenomenon: the presence of social media in adolescents life and their social interferences...